Importance of Increasing Modifiable Risk Factors Knowledge on Alzheimer’s Disease Among Community Pharmacists and General Practitioners in Spain - Alacreu, Mónica; Pardo, Juan; Azorín, María; Climent, María Teresa; Gasull, Vicente; Moreno, Lucrecia (Frontiers in Pharmacology, 2019)
Community pharmacists and general practitioners have daily contact with patients with Alzheimer’s disease (AD) but the number of positive cases constantly increases every day. Thus, the aim of this research is to describe the level of AD knowledge among community pharmacists and general practitioners in Spain, in order to see which are the most striking lacks to face with guaranties this conjuncture. Therefore a cross-sectional study has been carried out, using the Alzheimer's disease knowledge survey (ADKS), among members of the Spanish Society of Primary Care Physicians and the Spanish Society of Family and Community Pharmacy to discover it to report the differences in AD knowledge in both professional collectives. The ADKS has been responded by 578 community pharmacists and 104 general practitioners and consists of a battery of 30 questions, whose possible answers are true or false. It assesses the AD knowledge in seven areas (impact on the disease, risk factors, course of the disease, diagnosis, care, treatment and symptoms). Results indicate that Spanish pharmacists and general practitioners have a high score and personal knowledge of AD, nevertheless, it is not associated with greater awareness. Both scored above 80% at the categories: diagnostic, treatment and symptoms. However, lower knowledge level (60% of correct answers) was found to in those related to risk factors, such as the ignorance about hypercholesterolemia or hypertension as risk factors for the disease. Community pharmacists are already acting to control cardiovascular risk factors, but a wider knowledge of the relationship of these factors to AD is needed to act against these silent risk factors. Thus, pharmacists may also be involved in the management of AD that includes recognizing early symptoms for early detection of cognitive impairment. Hence, knowledge about risk factors is very important to develop this expanding role.